Addition Reactions of Me3SiCN with Aldehydes Catalyzed by Aluminum Complexes Containing in their Coordination Sphere O, S, and N Ligands. Issue 20 (8th April 2016) - Yang, Zhi; Yi, Yafei; Zhong, Mingdong; De, Sriman; Mondal, Totan; Koley, Debasis; Ma, Xiaoli; Zhang, Dongxiang; Roesky, Herbert W.
Abstract: The reaction of one equivalent of LAlH2 (1 ; L=HC(CMeNAr)2, Ar=2, 6‐ i Pr2 C6 H3, β‐diketiminate ligand) with two equivalents of 2‐mercapto‐4, 6‐dimethylpyrimidine hydrate resulted in LAl[(μ‐S)( m ‐C4 N2 H)(CH2 )2 ]2 (2 ) in good yield. Similarly, when N ‐2‐pyridylsalicylideneamine, N ‐(2, 6‐diisopropylphenyl)salicylaldimine, and ethyl 3‐amino‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐2‐carboxylate were used as starting materials, the corresponding products LAl[(μ‐O)( o ‐C6 H4 )CN(C5 NH4 )]2 (3 ), LAlH[(μ‐O)( o ‐C4 H4 )CN(2, 6‐ i Pr2 C6 H3 )] (4 ), and LAl[(μ‐NH)( o ‐C8 SH8 )(COOC2 H5 )]2 (5 ) were isolated. Compounds2 –5 were characterized by 1 H and 13 C NMR spectroscopy as well as by single‐crystal X‐ray structural analysis. Surprisingly, compounds2 –5 exhibit good catalytic activity in addition reactions of aldehydes with trimethylsilyl cyanide (TMSCN). Abstract : Four Lewis acidic aluminum compounds, LAl[(μ‐S)( m ‐C4 N2 H)(CH2 )2 ]2 (2 ), LAl[(μ‐O)( o ‐C6 H4 )CN(C5 NH4 )]2 (3 ), LAlH[(μ‐O)( o ‐C4 H4 )CN(2, 6‐ i Pr2 C6 H3 )] (4 ), and LAl[(μ‐NH)( o ‐C8 SH8 )(COOC2 H5 )]2 (5 ), were synthesized and fully characterized. They efficiently catalyze the addition reactions of trimethylsilyl cyanide to aldehydes. DFT studies reveal that the reaction proceeds through a stepwise mechanism where the C 1 −Si bond in the coordinated TMSCN is lengthened as a result of adequate charge separation between the C 1 and Si atoms.